Characterization and analysis of neurologic adverse events associated with COVID-19 vaccination (S12.006) - Boruah, Abhilasha; Westenberg, Erica; Khan, Abdul Hanif; Fan, Kee Hoo; Guekht, Alla; Spatola, Marianna; Calandri, Ismael; Netravathi, M; Wijeratne, Tissa; Warburton, Elyce; Doheim, Mohamed Fahmy; Pulickal, Carolin; et al. (Wolters Kluwer Health, 2022)
Objective: To characterize the incidence and spectrum of neurological adverse events (AE) after COVID-19 vaccination.